2010
DOI: 10.3340/jkns.2010.48.4.313
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Shunt Dependent Hydrocephalus after Treatment of Ruptured Intracranial Aneurysms : Surgical Clipping versus Endovascular Coiling According to Fisher Grading System

Abstract: Objective :The amount of hemorrhage observed on a brain computed tomography scan, or a patient's Fisher grade (FG), is a powerful risk factor for development of shunt dependent hydrocephlaus (SDHC). However, the influence of treatment modality (clipping versus coiling) on the rate of SDHC development has not been thoroughly investigated. Therefore, we compared the risk of SDHC in both treatment groups according to the amount of subarachnoid hemorrhage (SAH). Methods : We retrospectively reviewed 839 patients w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
13
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(16 citation statements)
references
References 21 publications
3
13
0
Order By: Relevance
“…The CSF in the ventricle will not affect the substance in the subarachnoid space too much, but overdrainage through the EVD may further worsen the compartmentalization. It is consistent with another study wherein, patients receiving continuous drainage from an EVD had a higher complication rate [3].…”
Section: Study Limitationssupporting
confidence: 89%
See 2 more Smart Citations
“…The CSF in the ventricle will not affect the substance in the subarachnoid space too much, but overdrainage through the EVD may further worsen the compartmentalization. It is consistent with another study wherein, patients receiving continuous drainage from an EVD had a higher complication rate [3].…”
Section: Study Limitationssupporting
confidence: 89%
“…However, evidence shows a higher complication rate in patients receiving continuous drainage from EVD [3]. Several studies also show decreased neurologic complication after SAH by continuous drainage through lumbar drain [3,4]. This study hypothesized that massive hemorrhage within the subarachnoid space may obstruct CSF outflow to the subarachnoid space and fresh CSF will no longer be flushed into the subarachnoid space though the openings in the fourth ventricle.…”
mentioning
confidence: 95%
See 1 more Smart Citation
“…However, this finding is inconsistent with those published in the current literature, where some studies have suggested that the number of patients undergoing VP shunts for hydrocephalus as a result of SAH may be reduced by proceeding with clipping instead of coiling. (13,14) However, a few papers have also cited otherwise. (15) A possible explanation for this variation could be that patients who were selected for endovascular coiling in our study generally had bettergrade aneurysms compared to those who underwent surgical clipping due to interventional radiologists having the first-line of selection of patients, thus resulting in better outcomes and lower rates of VP shunting.…”
Section: Discussionmentioning
confidence: 99%
“…Seven studies 14,16,20,23,[26][27][28] (1981 patients) reporting shunt-dependent hydrocephalus revealed no significant difference between clipping and coiling (16.4% versus 19.3%; OR, 0.84; 95% CI, 0.66-1.07; P=0.16) (Supplemental Figure 8). Three studies 6,11,12 (866 patients) revealed the procedural complications associated with poor outcome (Supplemental Figure 9), and the results between the 2 groups were comparable (9.9% versus 5.6%; OR, 1.19; 95% CI, 0.67-2.11; P=0.56).…”
Section: Secondary Outcomesmentioning
confidence: 99%